APLIKASI PENGHITUNG KALORI TERBAKAR SAAT BEROLAHRAGA SEPEDA MENGGUNAKAN GLOBAL POSITIONING SYSTEM (GPS) BERBASIS ANDROID - Fitriyanti, Aris Dwi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
Android technology development is very rapid, people used to aid activities in various fields, one of them in the field of sports. To maintain body condition in order to stay healthy in the midst of hectic activity, some people take the time and cost more to work out at the fitness center. But not infrequently they feel bored because it is always exercising indoors, it makes some people choose a sport that can give pleasure, lively sports are cycling a few years. Users can exercise bike burns calories by looking at the calories spent on the tool, because by looking at the sports activities we can evaluate how adaptable our sport. Given that problem, the application needed to help the public to remain able to evaluate and monitor their cycling activities such as speed, mileage, travel time, and calories burned anywhere. Android is rapidly evolving technology today, almost all mobile products now have the android operating system, and many are using this technology. Burned calorie counter app is based on Android that can be used anytime and anywhere they cycled, thus saving costs. The results of this study are expected to make the community more motivated to live a healthy lifestyle by exercising, people can evaluate their cycling activities at any time.Â Keywords: kalori terbakar, android, aplikasi, olahraga sepeda.